Gastric bypass after liver transplantation. Issue 12 (21st October 2013) - Al‐Nowaylati, Abdl‐Rawf; Al‐Haddad, Benjamin J. S.; Dorman, Rob B.; Alsaied, Osama A.; Lake, John R.; Chinnakotla, Srinath; Slusarek, Bridget M.; Sampson, Barbara K.; Ikramuddin, Sayeed; Buchwald, Henry; Leslie, Daniel B.
<x xml:space="preserve">Abstract</x> Few data are available for assessing the outcomes of bariatric surgery for patients who have undergone orthotopic liver transplantation (OLT). The University of Minnesota bariatric surgery database and transplant registry were retrospectively reviewed to identify patients who had undergone OLT and then open Roux‐en‐Y gastric bypass (RYGB) surgery between 2001 and 2009. Comorbidity‐appropriate laboratory values, body mass indices (BMIs), histopathology reports, and immunosuppressive regimens were collected. Seven patients were identified with a mean age of 55.4 ± 8.64 years and a mean follow‐up of 59.14 ± 41.49 months from the time of RYGB. The mean time between OLT and RYGB was 26.57 ± 8.12 months. The liver disease etiologies were hepatitis C (n = 4), jejunoileal bypass surgery (n = 1), hemangioendothelioma (n = 1), and alcoholic cirrhosis (n = 1). There were 2 deaths for patients with hepatitis C 6 and 9 months after bariatric surgery due to multiple‐organ dysfunction syndrome and metastatic esophageal squamous carcinoma, respectively. One patient with hepatitis C required a reversal of the RYGB because of malnutrition and an inability to tolerate oral intake. Four of the 7 patients had type 2 diabetes mellitus (T2DM), 4 had hypertension, and 6 patients had dyslipidemia. All patients were on immunosuppressive medications, but only 4 were on corticosteroids. Glycemic control was improved in all surviving patients with T2DM. The mean BMI was 34.27 ± 5.51 kg/m2 before OLT and 44.34 ± 6.08 kg/m2 before RYGB; it declined to 26.47 ± 5.53 kg/m2 after RYGB. In conclusion, in this case series of patients undergoing RYGB after OLT, we observed therapeutic weight loss, improved glycemic control, and improved high‐density lipoprotein levels in the presence of continued dyslipidemia. RYGB may have contributed to the death of 1 patient due to multiple‐organ dysfunction syndrome. Liver Transpl 19:1324–1329, 2013. © 2013 AASLD.